Pengaruh Kualitas Produk Dan Brand Image Handphone Samsung Terhadap Purchase Intention Konsumen Pada Galeri Teknologi Di Badung - Ni Ketut Budiani; Ni Wayan Ari Sudiartini; A.A Elik Astari; I Dewa Nyoman Usadha (Universitas Mahendradatta Denpasar, 2019)
This study aims to examine the effect of product quality and brand image of samsung mobile phone to purchase intention of consumer in Denpasar technology gallery. The tendency for product purchase intentions make the smart phone as a product aimed at the businessman who has a need for the Internet, there is no age limit or a job to be able to afford it. Public purchasing power is determined based on product quality and brand image of certain products that show the value of the purchased product.This study used 90 samples were taken using purposive sampling technique. The method of collecting data through questionnaire. Data analysis was performed with multiple linear regression analysis. The results showed by the F- test is product quality and brand image significant positive effect on purchase intention of consumer in technology gallery. The results showed by the coefficient of multiple correlation states is product quality and brand imagesimultaneous positive effect on purchase intention of consumer in technology gallery. Coefficient of determination was obtained equal to 58,2%. There is a partially significant influence between product quality and brand image in the technology gallery. The quality of products is the dominant variables that influence consumer purchase intention on technology gallery. Based on this suggested to the manufacturer Samsung to provide products that comply with the age of the user, such as parents need a keypad with large buttons. The producers through their business partners to create an image that is easily remembered by the public through media that has a wide network.